Issues Of Effective Use of Human Resources In Risk Management and It’s General Techniques - Xikmatullayevich, Kambarov Jamoliddin; Mahmudovna, Tashpulatova Munira (Journal of Advances in Accounting, Economics, and Management, 2024)
Risks are related to how company hire, retain, and manage employees and other types of workers, as well as employee behavior. Human resource risk management is about contemplating likely scenarios and outcomes so organization can minimize precarious situations, have adequate solutions in place, and even prevent difficulties from ever occurring.